The relationship between emotional exhaust with possible psychiatric disorders in medical students: Anxiety, Depression and Burnout - Almeida, Luiz Fernando Rodrigues de; Evangelista, Pedro Ferreira de Souza; Nogueira, Pietro de Brito; Silva, Rafael Correia de Sousa da (Research, Society and Development, 2023)
The Faculty of Medicine is recognized as an environment exposed to diverse and constant conditions that cause excessive stress, self-demand, demands from parents and impositions from the job market, regarding the quality of service and theoretical and practical knowledge. As a result, students in the health field, especially medicine, are more likely to develop symptoms of anxiety and depression during their studies. The percentage of the studied population that was affected by at least one form of Burnout was approximately 48.8%. Therefore, the present study aims to understand the spectrum of psychiatric manifestations in medical students and the consequences related to emotional exhaustion, based on searches in electronic databases. In students in the pre-clinical period, the prevalence of burnout was higher, due to the high level of stress perceived in the phase prior to entering medical school, due to the post-admission process, in which they experience a totally new environment, with competitiveness, lack of time or leisure activities and other factors that lead to emotional exhaustion. Students’ negative perceptions of balance and personal life during clinical rotations were related to high levels of burnout among students during their internships. However, the student’s gender did not influence this relationship. Therefore, there is a need for programs to enhance the student’s mental health throughout the entire training period, at different times of the year, so that there is early detection and interventions carried out.